Persistent pain and numbness in the extremities of an adult due to paraneoplastic peripheral neuropathy caused by olfactory neuroblastoma: A case report - Liang, Wenwen; Wang, Yanyan; Sun, Wenzhe; Li, Dongrui; Zhang, Xiaoping; Zhu, Pengcheng; Zhu, Zhou; Fang, Yongkang (Frontiers in Neurology, 2023)
Background: Paraneoplastic peripheral neuropathy (PPN) caused by olfactory neuroblastoma (ONB) has not yet been reported. Case report: We present a rare case of an adult who hospitalized repeatedly over the past nine months for persistent pain and numbness in the limbs. This patient was initially diagnosed with chronic inflammatory demyelinating polyneuropathy (CIDP) and treated accordingly, but neurological symptoms did not improve significantly. After this admission, FDG-PET/CT showed focal hypermetabolism of a soft-tissue mass in the nasal cavity, and further lesion biopsy suggested ONB. Combined with positive serum anti-Hu antibody, the diagnosis of PPN associated with ONB was eventually made. Furthermore, the patient's neurological symptoms were relieved after removal of the primary tumor, confirming the accuracy of the diagnosis. Conclusions: Our case not only expanded the clinical characteristics of ONB but also highlighted the importance of early and comprehensive tumor screening for the diagnosis of PPN.